Effect of flocculation of alumina slip on the pore size distribution of cast alumina by polyacrylamide (PAM) - Silakate P. (2014)
Tubular alumina filters were prepared by a slip casting process. The flocculation of alumina slip was studied as a function of pH and PAM concentrations. The particle size and viscosity of alumina slip were determined by using laser diffraction technique and Brookfield DV III+ viscometer, respectively. Pore size and pore size distribution of the alumina filters were measured by using Mercury Porosimeter. From the experimental results, the isoelectric point (i.e.p.) of the alumina slip showed at pH 7 and gave the largest particle size. Furthermore, the flocculation by PAM increased particle sizes, particle size distribution and viscosity of alumina slip due to polymer bridging on surface of particles. However, the addition of electrolyte in PAM solutions facilitate flocculation of particles due to the compression of electrical double layer and increase in the van der Waals attractive forces. The larger floc size resulted in bigger pore size in the filter. The average pore size of fired filter at 1500°C is in the range of 0.32 - 0.34μm.